Angiogenic Factors and Long-Term Cardiovascular Risk in Women That Developed Preeclampsia During Pregnancy. Issue 6 (December 2020) - Garrido-Gimenez, Carmen; Mendoza, Manel; Cruz-Lemini, Monica; Galian-Gay, Laura; Sanchez-Garcia, Olga; Granato, Chiara; Rodriguez-Sureda, Victor; Rodriguez-Palomares, Jose; Carreras-Moratonas, Elena; Cabero-Roura, Lluis; Llurba, Elisa; Alijotas-Reig, Jaume
Abstract : Preeclampsia is caused by placental impairment with increased expression of sFlt-1 (soluble fms-like tyrosine kinase 1) and decreased PlGF (placental growth factor); it has been associated with cardiovascular morbidity and mortality later in life, but the underlying mechanism remains unknown. The aim of this study was to determine whether sFlt-1 and PlGF levels during preeclampsia are associated to long-term cardiovascular risk. We prospectively recruited 43 women with previous preeclampsia and 21 controls with uncomplicated pregnancies. Cardiovascular risk assessment ≈12 years later included maternal hemodynamic, cardiac function and structure, biomarker analysis, and carotid-intima thickness evaluation. Women with previous preeclampsia had higher prevalence of hypertensive disorders and dyslipidemia than controls. In addition, they had worse global longitudinal strain, thicker left ventricular septal and posterior walls, more myocardial mass and increased carotid intima-media thickness compared with controls. PlGF during pregnancy correlated positively with high-density lipoprotein ( r =0.341; P =0.006), and negatively with global longitudinal strain ( r =−0.581; P <0.001), carotid intima-media thickness ( r =−0.251; P =0.045), and mean arterial blood pressure ( r =−0.252; P =0.045), when adjusted by study group. sFlt correlated negatively with high-density lipoprotein ( r =−0.372; P =0.002) and apolipoprotein A-1 ( r =−0.257; P =0.040), and positively with carotid intima-media thickness ( r =0.269; P =0.032) and left ventricular posterior wall thickness ( r =0.368; P =0.003). The antiangiogenic state present in preeclampsia is related to greater prevalence of cardiovascular risk factors ≈12 years after delivery. The knowledge of altered angiogenic factors may help detect women with a higher risk for premature cardiovascular disease, who will require earlier follow-up after delivery. Abstract : Supplemental Digital Content is available in the text.